Research Regarding Connections between Risks and Processes within Small and Medium Enterprises. (2015) - Dumitrescu, Andreea; Purcărea, Anca Alexandra; Negoiţă, Olivia Doina; Negoiţă, Octavian
Abstract: Business process approach is a current concern for many scholars and practitioners as the performance of any organization is directly influenced on how the objectives of these activities are achieved. The methodology framework consists of a literature review regarding the main concepts which are underlying the connection between risk and process. Main findings of the study will comprise of identifying the risks along with the trigger causes or circumstances and their potential effect not only on the activity, but also on the overall process. The importance to detect the risks whose impact has critical effect on the SMEs activity in terms of sustainable development and business continuity will be emphasized. In this respect, the potential processes highly exposed to risks are the most reliable indicators highlighting where an SME is vulnerable and to where should resources be directed to. A clear understanding of the types and intensity of the relationships and interactions between processes and their particular risks leads to cost effective decisions regarding undertaking long term mitigating strategies. The awareness of the link between different types of processes with their specific risks has become highly important as the overall vulnerability of an enterprise is enlarging in line with the business development.